2019
DOI: 10.1186/s12863-019-0764-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of inflorescence type markers by genotyping-by-sequencing of diploid and triploid F1 plants of Hydrangea macrophylla

Abstract: Background The ornamental crop Hydrangea macrophylla develops highly attractive lacecap (wild type) or mophead inflorescences. The mophead trait, which is mostly favored by consumers, is recessively inherited by the INFLORESCENCE TYPE locus ( INF ). If lacecap cultivars are crossed with mophead cultivars, then either 50% or all progenies develop lacecap inflorescences, depending on the zygosity at the IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In contrast, triploid plants have 2n = 3x = 54 chromosomes, and 2C DNA contents vary between 6.5 and 7.3 pg [6][7][8][9][10][11]. Recently, a cultivar has been found with a 2C DNA content of 8.9 pg, suggesting tetraploidy [12]. About 30 triploid cultivars were reported until now [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, triploid plants have 2n = 3x = 54 chromosomes, and 2C DNA contents vary between 6.5 and 7.3 pg [6][7][8][9][10][11]. Recently, a cultivar has been found with a 2C DNA content of 8.9 pg, suggesting tetraploidy [12]. About 30 triploid cultivars were reported until now [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the F1 population may have contained triploids due to unreduced gamete formation in the parents 45 . The presence of triploids in an F1 population has been linked to skewed segregation ratios 46 . Finally, the mismatch of genotype and phenotype could be due to the basic methodology of GBS.…”
Section: Discussionmentioning
confidence: 99%
“…An insertion of a long terminal repeat retrotransposon into the locus controlling inflorescence type was also proposed by the same research group through an observation of lacecap hydrangea cultivar mutation, but such a finding was not able to be connected to the current study due to limited genomic information. While genetic markers linked to inflorescence type in bigleaf hydrangea have been reported previously 46,50 , the single marker discovered and utilized herein has advantages for use in MAS. The previously published markers must be used in combination for marker-assisted selection while the SNP detailed here can be used alone.…”
Section: Discussionmentioning
confidence: 99%
“…Sympatry of different ploidy levels primarily arises through repeated formation of unreduced gametes by diploids (primary origin) or from secondary contact between previously allopatric diploid and polyploid populations (secondary origin; Petit et al, 1999). H. macrophylla shows both high rates of 2n gamete formation (Tränkner et al, 2019) and weak internal pre-zygotic reproductive barriers between ploidy levels as both diploids and triploids are nearly identical with respect to morphology, phenology, and likely habitat preferences (McClintock, 1957). The current study provides insight into a potential pre-zygotic barrier relating to pollen tube growth, where tubes of pollen from triploid parents grew more slowly than tubes of pollen from diploid parents, regardless of the ploidy level of the female parent.…”
Section: Pollen Tube Growthmentioning
confidence: 99%
“…macrophylla. An F1 mapping population from two diploid parents contained 103 diploids and 317 triploids (Tränkner et al, 2019). Alexander (2017) showed that controlled crosses using a cultivar known to produce unreduced male gametes resulted in 97% triploid offspring in the progeny.…”
Section: Possible Origin Of Triploid Cultivarsmentioning
confidence: 99%